Transsubstantiation: Jesu Christi Gegenwart in der Eucharistie aus römisch-katholischer Perspektive - Dahlke, Benjamin (Catholica <Münster>, 2023)
In order to describe the presence of Jesus Christ in the consecrated elements of bread and wine, the Catholic Church has adopted the term transsubstantiation. Coined in the Middle Ages, the term has been in use since the 13th century, both in theological discourse and in magisterial statements, in particular those issued by the Fourth Lateran Council and the Council of Trent. Despite the lasting factual significance and forma! bindingness of the doctrine of transubstantiation for Catholicism, it can be appreciated in a differentiated way. This includes recognizing that it has always been exposed to a variety of criticisms, both internally theologically and interconfessionally, because it met with massive rejection in connection with the Reformation. Displaying some criticisms thus may help to start an ecumenical discussion.